Immunophenotypic analysis of cerebrospinal fluid reveals concurrent development of ATL in the CNS of a HAM/TSP patient - Takeda, Reina (Int J Hematol, 2020)
Both adult T-cell leukemia/lymphoma (ATL) and human T-cell leukemia virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) can be induced by HTLV-1, but concurrent development has been rarely reported. We present the case of a 55-year-old female who developed cranial nerve symptoms after a 20-year history of HAM/TSP. Although multiple white matter lesions were observed on brain magnetic resonance imaging, no abnormalities were seen on a systemic computed tomography scan. Quantitative flow-cytometric analysis of cell populations in the cerebrospinal fluid (CSF) revealed that most of the infiltrating cells were not inflammatory cells, but HTLV-1-infected CD4(+) CADM-1(+) T-cells completely lacking CD7 expression. As stepwise downregulation of CD7 is correlated with disease progression from HTLV-1 carrier to aggressive ATL, the CSF cells were classified as aggressive ATL; these cells exhibited a more progressed phenotype than those in peripheral blood (PB). HAM/TSP disease activity was estimated to be low. From these and other examinations, we made a diagnosis of acute-type ATL, which unusually developed in the central nervous system at initial onset prior to systemic progression. In ATL cases with a challenging diagnosis, immunophenotypic characterization of CSF and PB is valuable for differential diagnosis and understanding disease status.